2009
DOI: 10.1002/adem.200900013
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of a Rabbit Ulna Bone Defect Using Bone Marrow Stromal Cells and a PLA/β‐TCP Composite by a Novel Sintering Method

Abstract: Bioceramic, synthetic, and natural polymers associated with cell adhesion and growth, have been used as matrices for bone tissue engineering. Successful bone regeneration depends on cellular interaction with these matrices. The purpose of this study was to fabricate polylactic acid (PLA)/ b-tricalcium phosphate (b-TCP) composites with a novel sintering method in order to enhance cellular interaction with matrices for bone regeneration. We prepared the composite by pressing and thermal treatment of the mixture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…It also improves tissue regeneration by enhancing cell attachment, proliferation, and differentiation. As we confirmed the effects of polylactic acid/beta-tricalcium phosphate (PLA/b-TCP) scaffold in our previous work, 25 we expected that the composite scaffold enhances osteogenic differentiation of recruited MSCs by increasing alkaline phosphatase (ALP) activity during tissue regeneration in the present system. This modified KLD12 peptide was evaluated for its ability to recruit MSCs and promote bone regeneration.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…It also improves tissue regeneration by enhancing cell attachment, proliferation, and differentiation. As we confirmed the effects of polylactic acid/beta-tricalcium phosphate (PLA/b-TCP) scaffold in our previous work, 25 we expected that the composite scaffold enhances osteogenic differentiation of recruited MSCs by increasing alkaline phosphatase (ALP) activity during tissue regeneration in the present system. This modified KLD12 peptide was evaluated for its ability to recruit MSCs and promote bone regeneration.…”
supporting
confidence: 89%
“…We confirmed that the b-TCP particles which were exposed on the surface of the scaffolds improved ALP activity and calcium deposition in our previous work. 25 Therefore, we expected that recruited MSCs by SP could be differentiated into osteocytes in this system. In the case of vascularized tissues, angiogenesis helps regenerate and maintain the tissue.…”
Section: Immunofluorescence Staining Of In Vivo Samplesmentioning
confidence: 98%
See 1 more Smart Citation
“…From the EDX analysis for identifying the particles, it was confirmed that the main atoms comprising the particles were Ca and P. It is thought that exposure to β-TCP particles affects calcium deposition and subsequent bone tissue formation. 19…”
Section: Resultsmentioning
confidence: 99%